Analysis of weaning‐induced stress in Saanen goat kids. Issue 4 (21st June 2012) - Magistrelli, D.; Aufy, A. A.; Pinotti, L.; Rosi, F.
Summary In young ruminants' life, weaning often coincides with a period of growth stasis and poor welfare. The present study aimed at evaluating the effect of coping with the new diet on behavioural and haematological stress indicators in goat kids subjected to a commonly adopted weaning practice. Immediately after birth, male Saanen goat kids were divided into two groups: MILK and WMIX. All were fed colostrum for the first 3 days and then goat milk to the age of 29 days. After that, MILK kids continued to receive milk, while the WMIX kids underwent weaning and were completely weaned by day 48. Animal behaviour was recorded daily. From day 23–50, blood samples were taken weekly and analysed for indicators of stress and immune function. No abnormal behaviour, such as injurious behaviours or stereotypies, was observed in either of the experimental groups throughout the experimental period. During the last week, fasting plasma cortisol level was significantly lower, whereas plasma activity of both alanine aminotransferase (ALT) and aspartate aminotransferase (AST) was significantly higher in WMIX kids, in relation to the MILK ones. Anyway, data were within the normal physiological range and no difference was observed neither in plasma haptoglobin, ceruloplasmin, albumin and antithrombin III, nor in plasma immunoglobulin A and G, at any time, signalling no stressful condition. Therefore, differences observed in cortisol, ALT and AST could be the consequence of the metabolic changes that occur during the transition from pre‐ruminant to ruminant state. The gradual weaning at 48 days of age did not result in any stressful condition and had no negative effect on weight gain. Results suggest that parameters commonly adopted to provide information on animal stress, such as cortisol and aminotransferase activity, can vary in relation to the physiological status of the animals and may bias stress assessment.